Genome-wide pan-GPCR cell libraries accelerate drug discovery - Yang, Hanting; Wang, Yongfu; Liu, Wei; He, Taiping; Liao, Jiayu; Qian, Zhongzhi; Zhao, Jinghao; Cong, Zhaotong; Sun, Dan; Liu, Zhixiang; Wang, Can; Zhu, Lingping; et al. (Acta pharmaceutica Sinica. B, 2024)
G protein-coupled receptors (GPCRs) are pivotal in mediating diverse physiological and pathological processes, rendering them promising targets for drug discovery. GPCRs account for about 40% of FDA-approved drugs, representing the most successful drug targets. However, only approximately 15% of the 800 human GPCRs are targeted by market drugs, leaving numerous opportunities for drug discovery among the remaining receptors. Cell expression systems play crucial roles in the GPCR drug discovery field, including novel target identification, structural and functional characterization, potential ligand screening, signal pathway elucidation, and drug safety evaluation. Here, we discuss the principles, applications, and limitations of widely used cell expression systems in GPCR-targeted drug discovery, GPCR function investigation, signal pathway characterization, and pharmacological property studies. We also propose three strategies for constructing genome-wide pan-GPCR cell libraries, which will provide a powerful platform for GPCR ligand screening, and facilitate the study of GPCR mechanisms and drug safety evaluation, ultimately accelerating the process of GPCR-targeted drug discovery. The genome-wide pan-GPCR cell line libraries, which utilize overexpression, PRESTO-Tango, and CRISPRa/i technologies, provide a powerful platform for GPCR-targeted drug discovery, which will facilitate the study of GPCR function, drug safety evaluation, and accelerate GPCR drug discovery. [Display omitted]